Examining a Reader's Meaning-Making Process of Picture Books Using Eye Movement Miscue Analysis. (November 2017) - Liwanag, Maria Perpetua Socorro U.; Martens, Prisca; Martens, Ray; Pelatti, Christina Yeager
The goal of this case study was to examine a second grader's reading of picture books using eye movement miscue analysis as a method to further understand reading as a meaning-making process. Two picture books with different relationships (e.g., enhanced and counterpoint) were selected because they elicit varied ways of presenting meaning and thus provide a unique opportunity to study reading. Findings from this case study highlight that reading is more than the eyes moving sequentially from word to word while the reader actively constructs meaning. Reading picture books demands an expanded repertoire of strategies since only looking at multimodal signs, such as written and pictorial cues, that are available when reading is not sufficient to ensure full comprehension of picture books. Implications for teaching reading and understanding multimodality in learning are addressed.